2015
DOI: 10.1007/s00240-015-0856-3
|View full text |Cite
|
Sign up to set email alerts
|

Extracorporeal shock wave lithotripsy in infants less than 12-month old

Abstract: There is a lack of literature on children compared to adults regarding the long-term effects of extracorporeal shock wave lithotripsy (SWL), specifically in infants. The aim of the present study was to analyze the efficacy and safety of SWL in infants and also evaluate its potential adverse effects in the mid-term. Between May 1999 and December 2013, 36 infants with 39 renal units underwent SWL treatment for kidney stones with an electrohydraulic lithotripter (Dornier MPL 9000/ELMED Multimed Classic). All chil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
11
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 19 publications
1
11
0
Order By: Relevance
“…In the literature, it is stated that the child's age is not a limiting factor for ESWL and that even infants can be treated easily. 10 In the present study, both univariate and multivariate analyses showed that the mean age of the children in the stone-free group was lower. Better success in these children may be due to decreased stone burden, softer stone composition, better ureteral compliance, and less distance between the shock wave generator and the stone.…”
Section: Discussionsupporting
confidence: 45%
“…In the literature, it is stated that the child's age is not a limiting factor for ESWL and that even infants can be treated easily. 10 In the present study, both univariate and multivariate analyses showed that the mean age of the children in the stone-free group was lower. Better success in these children may be due to decreased stone burden, softer stone composition, better ureteral compliance, and less distance between the shock wave generator and the stone.…”
Section: Discussionsupporting
confidence: 45%
“…Limited reports about ESWL in infancy exist because of the rarity of renal stones in infancy. The success rate of ESWL in infant patient was 84.6-100% ( 11 , 12 ). Despite these high stone free rate of the procedure, ESWL has some disadvantages such as requirement of anesthesia, ureteral obstruction in high volume renal stones and higher additional intervention rate ( 13 ).…”
Section: Discussionmentioning
confidence: 99%
“…Limited reports about ESWL in infancy exist because of the rarity of renal stones in infancy. The success rate of ESWL in infant patient was 84.6-100% (11,12). Despite these high stone free rate of the procedure, ESWL has some disadvantages such as requirement of anesthesia, ureteral obstruction in high volume renal stones and higher additional intervention rate (13).…”
Section: Discussionmentioning
confidence: 99%
“…Despite these high stone free rate of the procedure, ESWL has some disadvantages such as requirement of anesthesia, ureteral obstruction in high volume renal stones and higher additional intervention rate (13). In current literature ESWL is a safe method of treatment from the point of view of development of new onset diabetes mellitus and hypertension; however, long term detrimental effect of ESWL on kidney which can cause diabetes mellitus and hypertension is still controversial (12,14).…”
Section: Discussionmentioning
confidence: 99%